Elastic Wrapping of Lower Extremity Free Flaps during Dangling Improves Microcirculation and Reduces Pain as well as Edema - Kolbenschlag, Jonas; Ruikis, Alexandra; Faulhaber, Lisa; Daigeler, Adrien; Held, Manuel; Rothenberger, Jens; Lehnhardt, Marcus; Sogorski, Alexander; Goertz, Ole (Journal of Reconstructive Microsurgery, 2019)
Background Free tissue transfer has become a common and safe reconstructive procedure. However, total or partial flap losses remain a looming threat, especially for lower extremity free flaps due to the gravitational challenge associated with dependency. Thus, the majority of microsurgical centers apply some kind of structured flap training. However, due to the lack of evidence, these differ greatly, for example, in the application of an elastic wrapping during dangling. Therefore, the aim of this study was to assess the impact of an elastic wrapping on free flap microcirculation, edema, and pain during dangling.Methods Standardized dangling was performed from postoperative day (POD) 6 to 9 in 30 patients with microvascular reconstruction of the lower extremity. The first dangling per day was performed without elastic wrapping, followed by another session with 30 mm Hg of elastic wrapping. Tissue oxygen saturation (StO2), regional hemoglobin content (rHb), and blood flow (BF) were continuously measured in the free flap; the circumference of the flap as well as pain was assessed.Results During wrapped dangling, BF as well as StO2 was significantly increased, while rHb was significantly lower on all PODs. Wrapped dangling was rated significantly more comfortable and the girth of the free flaps was significantly less after wrapped dependency when compared with unwrapped dangling.Conclusion Dangling with an elastic wrapping with 30 mm Hg pressure improved flap microcirculation and reduced pain and edema formation.
Keywords: free flap; microcirculation; dangling; training; extremity; reconstruction; wrapping